2015
DOI: 10.1002/2015jb012016
|View full text |Cite
|
Sign up to set email alerts
|

The long‐wavelength geoid from three‐dimensional spherical models of thermal and thermochemical mantle convection

Abstract: The Earth's long‐wavelength geoid anomalies have long been used to constrain the dynamics and viscosity structure of the mantle in an isochemical, whole mantle convection model. However, there is strong evidence that the seismically observed large low shear velocity provinces (LLSVPs) in the lower mantle underneath the Pacific and Africa are chemically distinct and likely denser than the ambient mantle. In this study, we have formulated dynamically self‐consistent 3‐D spherical mantle convection models to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 85 publications
5
36
0
Order By: Relevance
“…In contrast, the overall density of the LLSVPs has been estimated by Koelemeijer et al () and Lau et al (), who argue for a neutral buoyancy of the LLSVP volume or a small excess density of about 0.5–1% in the lower part of the LLSVPs, respectively. This also agrees with geoid observations indicating that the upwelling material above the LLSVPs has to overcompensate dense material at the CMB to produce a geoid high (e.g., Liu & Zhong, ). However, these measured densities are smaller than those typically required for stability in numerical models of thermochemical convection, even when accounting for both chemical density and thermal expansion.…”
Section: Introductionsupporting
confidence: 88%
“…In contrast, the overall density of the LLSVPs has been estimated by Koelemeijer et al () and Lau et al (), who argue for a neutral buoyancy of the LLSVP volume or a small excess density of about 0.5–1% in the lower part of the LLSVPs, respectively. This also agrees with geoid observations indicating that the upwelling material above the LLSVPs has to overcompensate dense material at the CMB to produce a geoid high (e.g., Liu & Zhong, ). However, these measured densities are smaller than those typically required for stability in numerical models of thermochemical convection, even when accounting for both chemical density and thermal expansion.…”
Section: Introductionsupporting
confidence: 88%
“…For example, the model parameterization, including the number and depth of layers (Rudolph et al, 2015), or the smoothness of the viscosity (Constate, 1987) may affect the inversion. Possible composition heterogeneity in the mantle (Ballmer et al, 2015, Liu andZhong, 2015) may also affect the inversion. Also, due to the limitation of tomography models and the simplified mantle viscosity and temperature structure, high-accuracy residual topography at discrete observation points (Hoggard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They found that LLSVPs less dense than surrounding material fit better than denser LLSVPs. Moreover, by showing both good and bad fits to the data, they made a convincing case for low‐density LLSVPs, but as they admit, they “cannot rule out the presence of a ~100‐km‐thick denser‐than‐average basal structure.” Concurrently, using tides, Lau et al () concluded that the LLSVPs are 0.5% more dense than surroundings, though they admitted that most of the excess density “may be concentrated towards the very base of the mantle.” A safe summary might be that all data allow for a relatively dense D ″ beneath the LLSVPs, but at hundreds of kilometers above the core‐mantle boundary, the LLSVPs appear to be less dense than surrounding material, as suggested by bad fits presented by Koelemeijer et al () and by fits to the geoid (Liu & Zhong, , ).…”
Section: Whole‐mantle Convection and The Lower Mantlementioning
confidence: 99%